Spontaneous Resolution of a Traumatic Intracranial Aneurysm - de Jesus, Augusto Santos; Mendonça, Bernardo Keuffer; Costa, Camila Carvalhais (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2016)
Traumatic intracranial aneurysms are rare, and normally result from blunt or penetrating head traumas. Carotid angiography is considered the gold standard and reliable exam to detect this aneurysm. There are specific angiography features that mark the contrasts between a traumatic aneurysm and a common saccular aneurysm. Most authors agree that once the diagnosis is made, surgery is the ideal treatment. This article presents a case of a successful expectant treatment based on the clinical findings of the patient and combined with a constant evaluation of her case. The clinical findings depend on the location and direction of growth of the aneurysm. Traumatic aneurysms of the internal carotid artery (ICA) are unusual, and occur predominantly in the intracavernous portion of that vessel.
Keywords: brain injuries; intracranial aneurysm; craniocerebral trauma; cerebral angiography; spontaneous remission; carotid arteries